Problematic Criminalisation Of Moral Harassment At Work Socio-legal Study Page de garde, sommaire et éditorial - Fidma, Abdelhak (University of Eloued جامعة الوادي, 2022)
The subject of the present study is moral harassment in administrative organizations, as a negative phenomenon and deviation in behavior, from sociological, criminal, and legal perspectives. Simultaneously, it examines the issue of criminalizing the phenomenon in Algerian labor law compared to most European countries, which have already implemented texts that criminalize the phenomenon. The study examines various texts from different European countries’ legislations that prove the elements of moral harassment, as a crime, in order to alert the Algerian legislator, and responsible, relevant bodies, to take action and criminalize the phenomenon, which has become a living nightmare to the Algerian employee in their workplace. This phenomenon has proven to affect the performance of the employee, and threatens their psychological, and mental health, in addition to the deterioration of the public services, which in turn has become the object of protest by citizens. ملخص: تتناول هاته الدراسة ظاهرة التحرش المعنوي في التنظيمات الإدارية كظاهرة سلبية و انحراف في السلوك من وجهة نظر سوسيولوجية وجريمة من وجهة نظر قانونية حيث يبحث في مسالة تجريم الظاهرة في قانون العمل الجزائري مقارنة بأغلب الدول الأوروبية التي سبقت في وضع نصوص تجرمها بحيث يتعرض لمختلف النصوص في تشريعات عدد من الدول الأوروبية واثبات أركان جريمة التحرش المعنوي من اجل تنبيه المشرع الجزائري و الهيئات المختصة لاتخاذ موقف و تجريم الظاهرة و التي تشكل معاناة حقيقية للموظف الجزائري في العمل من خلال تأثيرها على أدائه وتهديدها لصحته النفسية والعقلية بالإضافة إلى تردي الخدمة العمومية التي أصبحت محل احتجاج من طرف المواطن
مقال
Keywords: harassment moral ; mobbing ; aggression ; work ; crime ; organization; التحرش المعنوي ; المهاجمه; عدوان; عمل; جرم; منظمة